Kyai's Visionary Leadership in the Development of Quality Management at the Annajah Purwokerto Islamic Boarding School - Muhammad Raais Doloh (CV. Edujavare Publishing, 2026)
This research discusses Kyai's visionary leadership in developing quality management at the Annajah Islamic Boarding School, Purwokerto. This research outlines the steps that must be taken by Kyai in creating, formulating, implementing and evaluating the vision of Islamic boarding schools. Kyai leadership plays a key role in forming an inspiring vision, communicating well, making wise decisions, and supervising and motivating Islamic boarding school stakeholders. Apart from that, quality management in Islamic boarding schools includes planning, organizing, mobilizing, supervising and assessing to improve the quality of Islamic boarding schools. This research uses a qualitative approach with descriptive methods. In data collection, the techniques used were observation, interviews and documentation. The results of data analysis show the important role of Kyai in achieving the vision of Islamic boarding schools and carrying out quality management for better Islamic boarding school development.